Предмет: Алгебра,
автор: iromashka01
Упростить выражение ( - - ) × ( - ) и найти его значение при t = -1,92
Ответы
Автор ответа:
0
1)t/(t²+2t+4)+(t²+8)/(t-2)(t²+2t+4)-1/(t-2)=(t²-2t+t²+8-t²-2t-4)/(t-2)(t²+2t+4)=
=(t²-4t+4)/(t-2)(t²+2t+4)=(t-2)²/(t-2)(t²+2t+4)=(t-2)/(t²+2t+4)
2)t²/(t-2)(t+2)+2/(t-2)=(t²+2t+4)/(t-2)(t+2)
3)(t-2)/(t²+2t+4)*(t²+2t+4)/(t-2)(t+2)=1/(t+2)
t=-1,92
1/(-1,92+2)=1/0,08=12,5
=(t²-4t+4)/(t-2)(t²+2t+4)=(t-2)²/(t-2)(t²+2t+4)=(t-2)/(t²+2t+4)
2)t²/(t-2)(t+2)+2/(t-2)=(t²+2t+4)/(t-2)(t+2)
3)(t-2)/(t²+2t+4)*(t²+2t+4)/(t-2)(t+2)=1/(t+2)
t=-1,92
1/(-1,92+2)=1/0,08=12,5
Похожие вопросы
Предмет: Українська мова,
автор: livakovskamasha
Предмет: Химия,
автор: dzonsnou218
Предмет: Геометрия,
автор: ddindon051
Предмет: Литература,
автор: somyantskaya
Предмет: Математика,
автор: egorbabinovich